Immediate effects of temporary bite-raising with light-cured orthodontic band cement on the electromyographic response of masticatory muscles (Journal of Applied Oral Science, 2022)
Objective: To assess the immediate effects of temporary bite-raising using light-cured orthodontic band cement on the superficial masseter and anterior temporalis electromyography (EMG) activity in healthy adults. Materials and Methods: Surface EMG signals were recorded bilaterally from the superficial masseter and anterior temporalis muscles of 30 volunteers with a normal occlusion, before and after having temporary bite-raising. The bite-raising was done by adding light-cured orthodontic band cement (3x5x2 mm WxLxH) on the lingual cusps of both upper first molars. The measurements were recorded (i) at rest, (ii) while clenching in centric occluding position and (iii) while chewing on an artificial test food. The EMG activity at rest and during clenching, the maximum voltage, and the duration of the identified EMG signal burst while chewing the artificial test food before and after temporary bite-raising were statistically compared using the paired t-test or the Wilcoxon signed-rank test based on the normality of the variables. The significance level was set at 5%. Results: After temporary bite-raising, we found no significant change in integral EMG activity at rest position for the superficial masseter (mean difference (MD)=7.5 μVs) and for the anterior temporalis muscle (MD=36.8 μVs); however, the integral EMG activity during clenching was significantly reduced for the superficial masseter (MD=201.2 μVs) and for the anterior temporalis muscle (MD=151.8 μVs). During mastication, the maximum voltage of the identified burst was significantly reduced on the preferred chewing side of the superficial masseter and anterior temporalis muscles (MD=127.9 and 47.7 μV, respectively), while no significant change was found for the duration of the identified burst (MD=-34.1 and 3.4 ms, respectively) after temporary bite-raising. Conclusion: The results point to an altered neuromuscular behavior during clenching and chewing immediately after temporary bite-raising with light-cured orthodontic band cement. This information is relevant for orthodontists to inform their patients what will happen to their masticatory muscle activity when this bite-raising method is used.